An Experimental Study on Unconfined Compressive Strength of Soft Soil-Cement Mixtures with or without GGBFS in the Coastal Area of Vietnam - Son Bui Truong; Nu Nguyen Thi; Duong Nguyen Thanh (Advances in Civil Engineering, 2020)
Soft soil is widely distributed in Vietnam, especially in the coastal area. In engineering practice, soft soil cannot be used to build any construction and needs to be improved or treated before building construction. In addition, Vietnam has many pig-iron or thermal power plants, which annually produce a huge amount of granulated blast furnace slag (GBFS). Thus, the use of this material for soft soil improvement needs to be considered. This paper presents experimental results on the unconfined compressive strength (UCS) of three Vietnam’s soft soils treated with Portland cement and Portland cement with ground granulated blast furnace slag (GGBFS). Binder dosage used in this study is 250, 300, and 350 kg/m3 with the three different water/cement ratios of 0.8, 0.9, and 1.0, respectively. The research results showed that the UCS of soil-cement mixtures depends on soil type, water/cement ratio, cement type, and binder content. Accordingly, the unconfined compressive strength increased with the increase of binder contents, the decrease of the natural water content of soft soil, water/cement ratios, and clay content. The highest value of UCS of treated soils was found for the soil at Site II with the Portland cement content, cement GGBFS, and water/cement ratio of 873 kg/m3, 2355 kg/m3, and 0.8, respectively. Besides, for all the three soils and two binder types, the water/cement ratio of 0.8 was found to be suitable to reach the highest UCS values of treated soil. The research results also showed that the UCS of treated soil with cement GGBFS was higher than that of treated soil with Portland cement. This indicated the effectiveness of the use of Portland cement with GGBFS in soft soil improvement. There is great potential for reducing the environmental problems regarding the waste materials from pig-iron plants in Vietnam and the construction cost as well.